Influence of Indigenous Radio Programme Contents on Voters' Participation and Voting Patterns in 2015 and 2019 Governorship Elections in Oyo State (Global Journal of Human-Social Science, 2025)
Several radio stations in South-Western Nigeria feature different indigenous radio programmes that contribute to the dissemination of diverse electioneering information. However, such indigenous radio programmes (IRG) are in most cases not likely to have been evaluated in terms of their influence on voters' participation considering high level of perceived apathy during previous elections in Nigeria. Therefore, this study investigated influence of indigenous radio programmes contents of Splash FM's Oro Sun Nu Kun and Lagelu 96.7 FM's Bo se nlo on voters' participation and voting patterns in the 2015 and 2019 governorship elections in Oyo State. The study adopted a triangulation mixed-methods design of the convergent approach. Sample comprised of 414 respondents, including key informants drawn from Akinyele and Lagelu Local Government Areas of Oyo State. Data was collected using three instruments; Indigenous Radio Programme Contents Analysis Checklist (InRaProCAC); Voters' Electoral Participation Questionnaire (VEPQ; r₌0.0) (0.760-0.861) and Key Electioneering Personalities Interview Schedule (KEPIS). Programme contents were analysed quantitatively, while survey data was analysed using descriptive and inferential statistics.
Keywords: radio broadcasting; radio programming; indigenous radio programmes